Revised Ordinances of 1892, of the City of Boston, and the Revised Regulations of 1892, of the Board of Aldermen of the City of Boston, Being the Eleventh Revision, Third Edition, Containing All Ordinances Passed Between March 3, 1892, and February 1, 1895, and All Regulations of the Board of Aldermen Passed Between July 22, 1892, and February 1, 1895, at p. 115 § 91 (1895) - (:unkn) unknown (General Publisher, 1895)
No person shall manufacture or sell, or expose for sale, any guncotton, nitro-glycerine, or any compounds of the same, nor any fulminate or substance, except gunpowder, intended to be used by exploding or igniting it, in order to produce a force to propel missiles, or to rend substances apart, except in accordance with a permit from the board of fire commissioners; nor shall any person send or carry through the public streets any such substance, except in the manner and in the quantities allowed by statute or ordinance.
--
Keywords: TRANSFER; MANUFACTURE & POSSESSION - TOYS AND EXPLOSIVES